PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI PENCEMARAN LINGKUNGAN TERHADAP HASIL BELAJAR SISWA SMAN 1 KUTACANE - Nursafiah, Nursafiah; Suriani, Halisah; Aswarita, Rika; Nurliza, Eli (Jurnal Dedikasi Pendidikan, 2022)
This study aims to determine differences in student learning outcomes of SMA N1 Kutacane among students who follow learning using Problem Based Learning and conventional learning. The problem in this research is the low of student learning outcomes on environmental pollution material in SMA N1 Kutacane. This study used experimental method. The population in this study is the students of class X which amounted to 240 students. The sample consisted of 68 students consisting of two classes, namely class X IPA1 with a total of 34 students as experimental class, and class X IPA2 with a total of 34 students as control class. Data was collected by pretest and postest. Improved learning result data is a normalized gain (N-Gain). The average difference of experimental and control class N-Gain was analyzed by independent sample t-test. The results showed that there are significant differences in student learning outcomes between the learning groups with Problem Based Learning model and group conventional learning. Result of t test show t value = 7,91 and t table value = 2,00 (t-count> t-table) at significant level 0,05.